1978
DOI: 10.2136/sssaj1978.03615995004200010033x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Deep Weathering Profile on Granite in Peninsular Malaysia: II. Mineralogy of the Clay, Silt, and Sand Fractions

Abstract: Different minerals characterize the three fractions in the different weathering zones. Halloysite in the clay fraction especially in the α and γ zones is due to a physical comminution of silt‐sized tubes. Strong peaks for halloysite (XRD) in the silt and sand fractions in these zones is shown (SEM) to be from partly altered feldspar fragments. Gibbsite is present mainly in the fine‐silt size and its presence in the sand in the α zone is due to cementation and aggregate formation. Aggregation of kaolinite also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Halloysite is a common weathering product of feldspars and biotite in granitic rocks, and usually occurs as randomly oriented felted masses or as radiating spherical aggregates (Eswaran and Bin, 1978;Keller, 1978;Kirkman, 1981;Anand et al, 1985). Radiating spherical aggregates of halloysite are believed to indicate that halloysite has crystallized from solution in a void (Banfield and Eggleton, 1990).…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Halloysite is a common weathering product of feldspars and biotite in granitic rocks, and usually occurs as randomly oriented felted masses or as radiating spherical aggregates (Eswaran and Bin, 1978;Keller, 1978;Kirkman, 1981;Anand et al, 1985). Radiating spherical aggregates of halloysite are believed to indicate that halloysite has crystallized from solution in a void (Banfield and Eggleton, 1990).…”
Section: Morphologymentioning
confidence: 99%
“…Halloysite has been reported to form by alteration of feldspars (Anand et al, 1985;Banfield and Eggleton, 1990), biotite (Eswaran and Bin, 1978), and volcanic glass (Kirkman, 1981). Halloysite derived from volcanic glass mostly exhibits a spheroidal crystal morphology whereas the dominant morphology of halloysite derived from crystalline minerals such as feldspars and micas is tubular.…”
Section: Introductionmentioning
confidence: 99%
“…Topotactic or epitactic alteration of mica or feldspar to halloysite has not previously been identified in nature (Gilkes et aL, 1986;Singh and Gilkes, 1992), whereas kaolinite formed from mica by topotactic alteration can subsequently produce halloysite tubes . Nevertheless, halloysite may also be formed through alteration of feldspar via solution or a non-crystalline intermediate stage (Eswaran and Bin, 1978;Singh and Gilkes, 1992). Robertson and Eggleton (1991) explained the transformation of platy kaolinite into spiral halloysite rods by a loss of structural rigidity at points along the kaolinite crystal due to hydration of kaolinite.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a decrease in the abundance ofhalloysite relative to that of kaolinite with an increase in degree of weathering of softs or with increasing proximity to the surface of soil profiles (Shimuzu, 1972;Eswaran and Wong, 1978;Calvert et al, 1980;Hughes, 1980;Hewitt and Churchman, 1982), Hence, it is tempting to infer that halloysite transforms to kaolinite with weathering. The apparently continuous series of X-ray powder diffraction (XRD) patterns of Ross and Kerr (1934) and Brindley and Robinson (1946) showing increasing order from halloysite to highly crystalline kaolinite also suggest a natural progression between halloysite and kaolinite.…”
Section: Introductionmentioning
confidence: 99%